Incidence of corneal pathologies in dogs - A retrospective prevalence study - K. Gayathri; C. Ramani; Mohamed Shafiuzama; GanneVenkata Sudhakar Rao; Ravi Sundar George (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The incidence of corneal pathologies was compiled for a period of two years from October 2015 to October 2017 by scrutinizing the hospital record of Ophthalmology unit, Department of Veterinary Surgery and Radiology, Madras Veterinary College Teaching Hospital. The rate of incidence of pathologies of the cornea was documented in terms of age, gender and breed of dogs. Incidences of corneal ulcers, descemetocele, staphyloma, non-inflammatory keratopathies,corneal dystrophies and degenerations, pigmentary keratitis and chronic superficial keratitis were documented. Analysis of prevalence of corneal ulcers in dogs with two previous time frames from the same region were also elicited.